2016
DOI: 10.1136/bjophthalmol-2016-308668
|View full text |Cite
|
Sign up to set email alerts
|

Five-year visual acuity outcomes and injection patterns in patients with pro-re-nata treatments for AMD, DME, RVO and myopic CNV

Abstract: BackgroundAnti vascular endothelial growth factor (VEGF) therapy is an established treatment for various retinal diseases. Long-term data on injection frequencies and visual acuity (VA), however, are still rare.MethodsFive-year analysis of real-life VA developments and injection patterns from 2072 patients (2577 eyes; 33 187 injections) with chronically active disease undergoing pro-re-nata treatment for age-related macular degeneration (AMD), diabetic macular oedema (DME), retinal vein occlusion (RVO) and myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
115
1
21

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(154 citation statements)
references
References 19 publications
11
115
1
21
Order By: Relevance
“…This observation is outlined very nicely in a recently published study. [20] In this retrospective study, nAMD patients received a median number of 6 injections during the first year of onset. Thereafter, the frequency of injections declined to 4 to 5 in the following 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is outlined very nicely in a recently published study. [20] In this retrospective study, nAMD patients received a median number of 6 injections during the first year of onset. Thereafter, the frequency of injections declined to 4 to 5 in the following 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…As a hypoxic retinal environment is common to DR, AMD, and ROP, the lessons from long-term anti-VEGF clinical trials for neovascular AMD could mirror what occurs in DR. Recent publications on anti-VEGF clinical trials have reached a consensus that, while the drugs may be effective in reducing BRB breakdown and in improving visual acuity in some patients, average gain of visual acuities has not been maintained for wet-AMD patients after 5-year anti-VEGF treatment, in which a sizable number of individuals have a significant reduction of visual acuity at the end of 5-year trials (57, 61) Such an outcome has also been observed in two 5-year DME clinical trials (62, 63). While the loss of visual acuity in wet-AMD and DME patients after long-term anti-VEGF therapies could be the consequence of many reasons, the loss of MG-specific VEGF signaling-mediated general retinal support could be a major one, which is supported by a striking resemblance between accelerated degeneration of all retinal neurons in diabetic/hypoxic MG-specific VEGFR2 KO mice and the abnormally thin retinas (thinning in all retinal layers) in a significant portion (36 percent) of the patients after 5-year anti-VEGF treatments for wet AMD (43, 57).…”
Section: Importance Of Vegf Signaling To Neuronal Function and Intmentioning
confidence: 99%
“…Hier kann eine feuchte Form mit Gefäßneu-bildungen (Neovaskularisationen, NV) von einer trockenen Form mit flächigem Untergang des RPE (geographische Atrophie [GA]) unterschieden werden, wobei beide Formen zum unwiederbringlichen Verlust von Photorezeptoren führen [9]. Therapien existieren bislang nur für die feuchte, neovaskuläre Form [9,11], diese sind lediglich symptomatisch und nicht kausal: Es werden Inhibitoren des Vascular Endothelial Growth Factors (VEGF) mittels intravitrealer Injektion appliziert. Die Behandlung muss allerdings regelmäßig wiederholt werden (durchschnittlich fünfmal im Jahr, im Einzelfall deutlich häufiger) [11], verursacht hohen Aufwand und Kosten und kann den Krankheitsverlauf nur verlangsamen, nicht komplett aufhalten oder gar umkehren [9,11].…”
Section: Der Augenhintergrund Als Geeigneter Ort Für Zelltherapieunclassified
“…Therapien existieren bislang nur für die feuchte, neovaskuläre Form [9,11], diese sind lediglich symptomatisch und nicht kausal: Es werden Inhibitoren des Vascular Endothelial Growth Factors (VEGF) mittels intravitrealer Injektion appliziert. Die Behandlung muss allerdings regelmäßig wiederholt werden (durchschnittlich fünfmal im Jahr, im Einzelfall deutlich häufiger) [11], verursacht hohen Aufwand und Kosten und kann den Krankheitsverlauf nur verlangsamen, nicht komplett aufhalten oder gar umkehren [9,11]. Risikofaktoren für die Entstehung oder Progression der AMD sind in erster Linie hohes Alter: Die Prävalenz der späten AMD nimmt deutlich zu bei über 70-Jährigen und liegt in dieser Altersgruppe bei 10-20 % [9,12,13].…”
Section: Der Augenhintergrund Als Geeigneter Ort Für Zelltherapieunclassified